Gender perception and experience about public space: A study of Varanasi city - Neha Kushwaha; Jagadish Singh (National Geographical Journal of India, 2022)
Space constitutes an important part of an individual’s Both men and women use space but their perceptions and experiences varied differently. In everyday life, gender and gendered space can be recognized, accepted, and experienced differently in public and private spaces depending upon comments and harassment. The study attempts to analyze the spatial pattern of gender-based perception toward public space in Varanasi city, one of the oldest living cities in the world. The study is based on primary data collected from a survey of 400 households. The chi-square test has been used to draw inferences. To understand the level of perception and experiences, a composite index of selected variables is used. The analysis indicates that all male respondents enjoy the freedom to go out for work, while, only 74.9 percent of females have this liberty. Rest 25.1 percent of female respondents are not allowed or restricted to go outside. This shows a patriarchal mindset that exists in the city, with male dominance in public spaces, and in social rituals, and activities more than women.